1997
DOI: 10.1021/la9704415
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the C−C Bond during the Electrooxidation of 1-Propanol and 2-Propanol:  Effect of the Pt Morphology and of Codeposited Ru

Abstract: The electrooxidation of 0.1 M 1-propanol and 2-propanol in 0.1 M HClO4 on smooth Pt and electrodeposited Pt and Pt0.89Ru0.11 was studied by cyclic voltammetry and in situ Fourier transform infrared spectroscopy (FTIRS). On smooth Pt, CO2 as well as partially oxidized products (propionic acid from 1-propanol and acetone from 2-propanol) was detected. A strong catalytic enhancement toward the oxidation to CO2 is observed on electrodeposited Pt for both 2-propanol and 1-propanol, thus showing the effect of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 21 publications
4
57
1
1
Order By: Relevance
“…Nevertheless, the most important fact is that in contrast to the primary alcohols no adsorbed CO is detected [79,80]. Even though small amounts of CO 2 have been observed [78] it has been formed without the CO ads intermediate that is considered to be a strong catalyst poison at low potentials.…”
Section: Isopropanolmentioning
confidence: 99%
“…Nevertheless, the most important fact is that in contrast to the primary alcohols no adsorbed CO is detected [79,80]. Even though small amounts of CO 2 have been observed [78] it has been formed without the CO ads intermediate that is considered to be a strong catalyst poison at low potentials.…”
Section: Isopropanolmentioning
confidence: 99%
“…7a, b), while the oxidation current density of 2-propanol is higher at Pt modified electrodes compared to the Ti modified electrodes, in addition the stability of the modified Pt electrodes over repeated cyclization is higher than that of the Ti modified electrodes ( Table 4). The main product in the oxidation of 2-propanol is acetone due to the difficult breaking of C-C bond [38], in addition to CO 2 [12]. Oxidation of 2-propanol involves 18 electron transfers, so the process is very complicated, also, it displays the multiple oxidation peaks especially on the modified Ti substrates and multiple reoxidation peaks which indicates the complexity of the adsorbed reaction intermediates [17].…”
Section: Electrooxidation Of 2-propanolmentioning
confidence: 99%
“…Ethanol is an alternative choice as a fuel due to its non-toxicity and availability from biomass resources [3,9,10]. Also the recent studies have focused on 2-propanol as an alcohol's fuel because it shows a lower overpotential and higher performance than methanol [8,11,12]. Alcohols with more than two carbon atoms have several isomers and special features of non-CO adsorption [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al [38] suggested that the presence of the OH group in the primary alcohol strongly favors the rupture of the C3 chain during electroreduction, yielding hydrocarbon-type adsorbates with C2 and C3 chains. On the other hand, the rupture of the carbon chain is unfavorable when the OH group is attached to the central C-atom of 2-propanol.…”
Section: Xpsmentioning
confidence: 99%